(untitled) - Cecil, Robert D. (San Francisco, CA, 2007)
This innovative, comprehensive, and fully integrated management development program provides a vehicle for enabling managers and leaders to participate more effectively in their organization's OD processes. The concepts, models, tools, and other materials have been used successfully to train managers, leaders, and MD/OD personnel in organizations such as IBM, AT&T, Kraft, Baxter Labs, Sears, Caterpiller, and the U.S. Navy, Army, and Air Force. The accompanying CD-ROM contains customizable tools for OD consultants and facilitators as well as additional chapter material.
Keywords: Management,Quản trị,Quản trị,Executives; Study and teaching,Tập huấn,Dạy và học,Training of